POTRET PAHLAWAN DALAM KARYA TAPESTRI - FITRIA ERVIANI, Drs. Erwin A, M.Sn., Dra. Ernis, M.Pd. (Universitas Negeri Padang, 2017)
The purpose of making this final work is for creating seven potraits Indonesian’s heroes of dashing tapestry techiques. With reason because of sacrifices, stuggles, and actions that giving meaning and benefits for society. Other reason, today the younger generations are less appreciative of the heroes and their sense of nationalism is fading away. Therefore, the author takes a theme about as a subject in this work. The method of creation processnof work : first, preparation bay way doing observatio. The second, elaboration, third, syinthesis stage, fourth, concept realization that making sketches, process of work, and finishing. Fifth, the completion is done exhibition and making the catalog and the report.The work’s result, the portrais of indonesian’s heroes are Raden Ajeng Kartini, Cut Nyak Meutia, Sultan Hasanudin, General Sudirman, Imam Bonjol, Ir. Soekarno, and Teuku Umar. It is hoped that the final work will be beneficial for art’s students, as a material of appreciation and to be comparasion for creating tapestry’s better in the future.Keywords : Heroes’s portraits, tapestry 1